The Effect of Wayang Huruf Interactive Learning Media on Letter Recognition Skills in Children Aged 4–5 Years - Mutiara; Herman; Harlisa Harianti; Muharram; Yusnia (Universitas PGRI Madiun, 2026)
Early childhood literacy development is in its initial stages and remains heavily influenced by learning experiences that are concrete, repetitive, interactive, and aligned with children's developmental characteristics. This study aims to examine the impact of interactive learning media specifically